1998
DOI: 10.1042/cs0940359
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Ventricular Adrenomedullin and Atrial Natriuretic Peptide Gene Expression in Pressure and Volume Overload in the Rat

Abstract: 1. Adrenomedullin is a recently discovered vasodilating and natriuretic peptide whose physiological and pathophysiological roles remain to be established. Like atrial natiuretic peptide adrenomedullin is expressed in the left ventricle. Ventricular expression of atrial natriuretic peptide is known to be markedly increased by volume or pressure overload. In this study we investigated whether ventricular expression of adrenomedullin is similarly stimulated under such conditions. 2. Ventricular adrenomedullin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
4
14
1
Order By: Relevance
“…They have suggested that mechanical wall stress is not an important regulator of cardiac AM expression, which might be due to a difference in the magnitude of POL. Although both studies used abdominal aortic-banded rat models, POL in the model of the present study was more severe than in that of Kaiser et al 7 In the present study, the ratios of LV weight corrected for body weight over 14 days after surgery were obviously higher than those in the study of Kaiser et al 7 The pressure loading in their study might have been insufficient to activate the induction of AM gene expression.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…They have suggested that mechanical wall stress is not an important regulator of cardiac AM expression, which might be due to a difference in the magnitude of POL. Although both studies used abdominal aortic-banded rat models, POL in the model of the present study was more severe than in that of Kaiser et al 7 In the present study, the ratios of LV weight corrected for body weight over 14 days after surgery were obviously higher than those in the study of Kaiser et al 7 The pressure loading in their study might have been insufficient to activate the induction of AM gene expression.…”
Section: Discussioncontrasting
confidence: 55%
“…However, whether or not acute POL increases cardiac AM transcription remains controversial. [7][8][9] The results of the present study revealed that LV AM expression increased on day 1 then declined, and that it was not significant 5 or 14 days after acute aortic banding. Right ventricular AM gene expression also increased on days 1 and 5, but not on day 14.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To monitor the development and regression of myocardial hypertrophy at the molecular level, we measured the LV expression of atrial natriuretic factor (ANF) mRNA. 23,24 Our results indicated that short-term treatment with ramipril reduced susceptibility to reperfusion-induced ventricular fibrillation (VF) in hearts with established LV hypertrophy. Furthermore, this protection was achieved without a reduction in LV mass (but an increase in hydroxyproline content) and was accompanied by the regression of myocyte hypertrophy, as reflected by cellular and molecular indices.…”
mentioning
confidence: 81%
“…Furthermore, to monitor the development of myocardial hypertrophy at the molecular level, we measured LV expression of atrial natriuretic factor (ANF) mRNA. 11,12) …”
mentioning
confidence: 99%